Urban precarity and youth mental health: An interpretive scoping review of emerging approaches. (March 2023) - Pykett, Jessica; Campbell, Niyah; Fenton, Sarah-Jane; Gagen, Elizabeth; Lavis, Anna; Newbigging, Karen; Parkin, Verity; Williams, Jessy; ,
Abstract: Circumstances of living are key to shaping emotional and affective experiences, long term health, wellbeing and opportunities. In an era characterised by rapid urbanisation across the majority of the world, there is increasing interest in the interaction between mental health and urban environments, but insufficient attention is paid to how mental health is situated in space and time. Socio-economic inequalities are prevalent in many urban environments globally, making conditions of living highly precarious for some social groups including young people. There remains a large volume of unmet mental health service needs, and young people are impacted by uncertain economic futures. The purpose of this scoping review is to develop an interdisciplinary and globally-informed understanding of the urban conditions which affect youth mental health across a range of scales, and to identify protective factors which can promote better youth mental health. We seek to broaden the scope of urban mental health research beyond the physical features of urban environments to develop an interpretive framework based on perspectives shared by young people. We illustrate how concepts from social theory can be used as an integrative framework to emphasise both young people's lived experiences and the wider cultural and political dynamics of urban mental health. Highlights: An interdisciplinary theoretical framework on youth mental health in cities. Interpretative scoping review of urban mental health literature co-produced with youth advisors. Investigates conditions of urban precarity, processes and protective factors. Identifies research gap on the distant factors influencing youth mental health. Neuropolis and ontological insecurity inform conceptual analysis of lived experiences.